Level of knowledge and awareness among parents regarding the care of children with thalassaemia - Makajil, Johari Daud; Taising, Zerah; Thomas, Deena Clare; Nain, Rose A (UNUSA Press, 2024)
Background This study assessed parental knowledge and awareness of children with thalassemia. Thalassemia care among 65 parents at a Kota Kinabalu hospital focuses on parental knowledge and awareness of children with thalassemia. The objectives were to identify parents' level of knowledge of thalassemia care and assess their awareness of specific care needs. Methods: This was a descriptive, cross-sectional study of the thalassemia families of patients at Likas Women and Children's Hospital, Kota Kinabalu, Sabah. Using random sampling. The study involved 65 respondents from Sabah Women and Children in Kota Kinabalu, Sabah. Data from questionnaires and tests were processed using SPSS version 24, with descriptive statistics analysing frequency and percentage, expressed as mean ± standard deviation. Results Most respondents had a high level of knowledge about thalassemia, an inherited disease caused by insufficient red blood cell supply. They understood that untreated conditions could deteriorate thalassemia patients but could lead normal lives with proper therapy. They also knew that thalassemia could be detected through blood tests and that blood donation could be beneficial. However, they had moderate knowledge of the connection between thalassemia and anaemia, blood transfusions as the only treatment, and their ability to identify and avoid thalassemia during pregnancy. Conclusion This study emphasises the need for education, community engagement, and healthcare involvement to enhance the understanding and support of individuals with thalassemia, suggesting that comprehensive strategies, including education programs and collaborations with local organisations, can be implemented.